2015
DOI: 10.1177/0047287515608504
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Outbound Tourism Research

Abstract: When people choose they often prefer similarity, rather than complementarity. This paper argues that the evaluation of a holiday destination is no exception to this tendency. The study introduces tourist-destination personality similarity (TDPS) as a concept that is distinct from perceived overall fit (POF) between tourist and destination, and examines the effects of these two concepts of congruence on vacationers' satisfaction and recommendation behavior. Examining a sample of actual vacationers (N = 308) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 120 publications
(166 reference statements)
0
85
0
Order By: Relevance
“…China has become the world's largest source market for international tourists since 2012 (UNWTO, 2018), attracting global industry and academic research attention. Studies on Chinese outbound tourism concerning their motivations, expectations, travel restrictions, and behavioral issues increased significantly in the last decade (Jin & Wang, 2016), however few studies have explored the political dimensions that affect the market development and tourism demand at a regional level.…”
Section: Introductionmentioning
confidence: 99%
“…China has become the world's largest source market for international tourists since 2012 (UNWTO, 2018), attracting global industry and academic research attention. Studies on Chinese outbound tourism concerning their motivations, expectations, travel restrictions, and behavioral issues increased significantly in the last decade (Jin & Wang, 2016), however few studies have explored the political dimensions that affect the market development and tourism demand at a regional level.…”
Section: Introductionmentioning
confidence: 99%
“…The scope of their review is much wider than in the previous reviews cited above which indicates a significant growth of research in the field within this five year period. Jin and Wang (2016) found that research efforts continued to concentrate in areas such as travel motivation, expectations, travel barriers, destination image and preference, market segmentation, and business management issues. They recognized that alongside the growth of the market, future research is needed on the platforms of sustainability and ethics.…”
Section: Studies On Chinese Outbound Tourismmentioning
confidence: 99%
“…Young Chinese tourists have more experience in international travel, and they are beginning to embrace diff erent consumption patterns. For example, the earlier tourists were primarily motivated by their appreciation of modernity; Now they already benefi t from modernity in their daily lives in China and they thus value what they do not have in their own country, such as clean and pollution-free natural landscapes (Jin & Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lojo and Li (2018) indicate that most previous studies fail to show the diff erences between diff erent tourism segments. In addition, reviews of the academic literature on Chinese tourism (Jin & Wang, 2016;Jørgensen, Law, & King, 2016;Lojo, 2016b;Lojo, Li, & Cànoves, 2019) indicate that Europe and European countries are destinations in which Chinese tourism has not been suffi ciently studied.…”
Section: Introductionmentioning
confidence: 99%